2015
DOI: 10.5812/archneurosci.32127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations of 176 Cases of Primary Central Nervous System Lymphoma: A Case Series

Abstract: Background: Primary central nervous system lymphoma (PCNSL) is a malignant tumor, the incidence of which has been increasing in immune compromised patients during the last two decades. Objectives: This study was conducted to determine the most prevalent clinical presenting symptoms of PCNSL patients. Patients and Methods: In this retrospective descriptive study, all PCNSL patients' data over a 25-year period (1990-2014) were assessed. PCNSL was confirmed pathologically after stereotactic biopsy in the Neurosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…A typical presentation will depend on localization, seizures, motor, sensory deficits, and depressed level of consciousness if ICP is high. Localization is most common supratentorial in more than 80% of cases, being periventricular white matter and basal ganglia, the most commonly reported followed by ependymal extension, the later of great importance for differential diagnosis in imaging [17][18][19]. Classical MRI appearance shows single or multiple lesions isointense or hypointense in T1WI, homogenously isointense or hypointense to the cortex in T2 and enhancing lesion with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…A typical presentation will depend on localization, seizures, motor, sensory deficits, and depressed level of consciousness if ICP is high. Localization is most common supratentorial in more than 80% of cases, being periventricular white matter and basal ganglia, the most commonly reported followed by ependymal extension, the later of great importance for differential diagnosis in imaging [17][18][19]. Classical MRI appearance shows single or multiple lesions isointense or hypointense in T1WI, homogenously isointense or hypointense to the cortex in T2 and enhancing lesion with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Patients can also present with symptoms due to leptomeningeal involvement with neuronal lymphomatosis as the sole manifestation, such as headache, difficulty speaking, altered mental status, seizures and weakness. Additional presenting symptoms include signs of elevated intracranial pressure, 6th nerve palsy, bilateral 3rd nerve palsy, mononeuritis multiplex, unilateral hearing loss, and bilateral 7th nerve paralysis [24]. A cross-sectional retrospective study conducted in Shohadaye Tajrish Hospital in Tehran, Iran, during a 25-year period (1990 -2014) showed that symptoms are often widespread and multifocal.…”
Section: Presenting Symptomsmentioning
confidence: 99%
“…It could be a single tumor or a multifocal disease. The most common site is a space occupying parenchymal mass [24]. On imaging, there is no definitive pattern for diagnosis and reactive processes cannot be ruled out.…”
Section: Diagnosis and Its Pitfallmentioning
confidence: 99%
“…PCNSL most commonly involves the periventricular white matter (51%) and basal ganglia (48.9%). The most frequent presenting symptoms were shown to be hemiparesis (56.2%) and headache (51.7%) in a retrospective study of 176 patients with PCNSL (7). Other common symptoms include neuropsychiatric symptoms and other signs of raised intracranial pressure (i.e.…”
mentioning
confidence: 99%